Acoustic performance of cooling towers on neighbor residential building and noise reduction methods - S. Seddeq, H.; M. Abdel-Aziz, A.; El-Sayed Shalaby, Mahfouz.; Y. Elmasry, A. (International Journal of Engineering and Technology, 2019)
The purpose of this research is to present an assessment of the noise impact of cooling equipment and determine if the noise levels comply with the permissible limits or not. Also, it presents two calculation methods to predict the acoustic performance of the cooling towers on a neighbor residential building. Comparison of the actual measurements vs. the predicted levels was carried out to select the appropriate calculation method to perform analysis for different noise reduction techniques and determines the best way to achieve the acceptable noise criteria. The results showed that the most effective methods for noise control are obtained by using variable frequency control for the cooling tower fans and lined plenum champers together or individual.Â